VIOLÊNCIA: VIZINHA OU HABITANTE DO MESMO ESPAÇO? - Júlio Gomes de Almeida (EccoS – Revista Científica)
This article presents aspects of the topic "school violence" based on discussions made about it in meetings which happened in the Research and Study about Formation in Organizational Environment Center connected with the research approach: Subject, Formation and Learning from the Master Program in Education from the São Paulo University. The discussion about this topic arose in the meetings in the Center. Therefore, it revisits some discussions and presents new questions to the view in which the violence is outside and enters in the school at certain careless moments, and emphasizes the understanding in which the violence is also produced and reproduced in the relationships that happen in the school routine. Through the presentation of every day situations, it tries to show that some school practices must be rethought.